A simple voltammetric determination of metsulfuron-methyl in water samples using differential pulse cathodic stripping voltammetry - Thanalechumi, P. (Pesticide Science Society of Japan, 2017)
The voltammetric determination of metsulfuron-methyl, a type of pesticide, was investigated on a hanging mercury drop electrode using a differential pulse cathodic stripping voltammetry technique. The experimental parameters, such as the pH of the Britton-Robinson buffer, accumulation time, accumulation potential and initial potential were optimized for the metsulfuronmethyl determination. A well-defined reduction peak was observed at pH 2.0 to 4.0 in the potential range of -0.75 to -1.0 V. The pH of 2.0 was chosen as the optimum pH due to a good stripping signal of the reduction peak. There were no significant interfering ion effects on the electroanalysis of metsulfuron-methyl. The optimized parameters were then used to determine metsulfuron-methyl in the commercial pesticide Ally. The proposed method was highly sensitive due to the lower limit of determination (0.04 mg/L), being relatively selective, and consisting of good precision. The recovery values achieved were about 93% in water samples for this analysis.